2018
DOI: 10.1016/j.jaip.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Evaluation of Chronic Rhinosinusitis Symptoms in a Population-Based Sample

Abstract: Less than half with nasal and sinus symptoms meeting CRS EPOS criteria in our general, regional population had symptom persistence over time, with symptom profiles at baseline and age of onset being strongly associated with stability of symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…However, this could still result in large differences in proportions meeting EPOS s criteria for CRS over time and lead to misclassification of CRS status when symptoms are assessed at cross section. For example, we have previously reported that, among subjects who met EPOS s current CRS at baseline, almost half did not meet criteria for current CRS 6 months later . The latent constructs, however, were stable over time.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…However, this could still result in large differences in proportions meeting EPOS s criteria for CRS over time and lead to misclassification of CRS status when symptoms are assessed at cross section. For example, we have previously reported that, among subjects who met EPOS s current CRS at baseline, almost half did not meet criteria for current CRS 6 months later . The latent constructs, however, were stable over time.…”
Section: Discussionmentioning
confidence: 95%
“…The questionnaires included items on the presence, frequency, severity, and bother of a range of symptoms associated with sinonasal disease and comorbid conditions (Table ) . Each questionnaire included 37 questions in common with the same response options (how often the symptom occurred in the past 3 months as 1 = never, 2 = once in a while, 3 = some of the time, 4 = most of the time, or 5 = all the time; Table ).…”
Section: Methodsmentioning
confidence: 99%
“…Demographic data were obtained from electronic health records. Migraine headache, asthma, and anxiety sensitivity index (ASI) data were collected via CRISP questionnaires . Migraine headache status was based on the ID Migraine questionnaire, and asthma was based on self‐report of a doctor diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…In a longitudinal study of adults reporting CRS symptoms in a US general population, the lifetime prevalence of CRS was estimated to be 27.5% with an annual cumulative incidence of almost 2%. 25 As a comparison, the lifetime prevalence of asthma in adults was 13.9% according to the 2016 National Health Interview Survey. 7 The annual cost of these diseases has been estimated to be between $22 to $33 billion for CRS [26][27][28] and $81.9 billion for asthma.…”
Section: Chronic Rhinosinusitismentioning
confidence: 99%